Alkali Metal Chlorine and Bromine Carbenoids: Their Thermal Stability and Structural Properties. Issue 50 (11th July 2017) - Molitor, Sebastian; Gessner, Viktoria H.
Abstract: The synthesis and structures of a series of M/X carbenoids of the type [Ph2 P(S)]2 CMX with M=Li, Na, and K and X=Cl and Br are reported, amongst the first isolated Na/Br and K/Br carbenoids. NMR spectroscopic as well as crystallographic studies showed distinct differences between the lithium carbenoids and their heavier congeners. In the solid state, all carbenoids showed no direct metal–carbon interaction, but an interaction between the metal and the halogen atom. This contact is only very weak in the case of the Li/Br carbenoid, but much more pronounced in the corresponding potassium and sodium compounds. Nevertheless, these interactions did not significantly influence the stability of the carbenoids by weakening the C−X bond and facilitating the MX elimination. As such all compounds were found to be stable up to approximately 60 °C in solution. Hence, M−X interactions—albeit being an essential feature for the structure formation of carbenoids—are not the only criterion determining the stability of such compounds. In the present systems, the stabilization by the thiophosphinoyl moieties is more important than the metal/halogen combination. Abstract : Room‐temperature stable carbenoids with different metal/halogen combinations were isolated and characterized, amongst the first sodium and potassium bromine systems. Metal–halogen interactions were found to be important factors for structure formation, but did not significantly influence the stability of the carbenoids.